2015
DOI: 10.1115/1.4028823
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Individual Trabecular Repair and Its Mechanical Implications in Parathyroid Hormone and Alendronate Treated Rat Tibial Bone

Abstract: Combined parathyroid hormone (PTH) and bisphosphonate (alendronate-ALN) therapy has recently been shown to increase bone volume fraction and plate-like trabecular structure beyond either monotherapy. To identify the mechanism through which plate-like structure was enhanced, we used in vivo microcomputed tomography (lCT) of the proximal tibia metaphysis and individual trabecular dynamics (ITD) analysis to quantify connectivity repair (incidences of rod connection and plate perforation filling) and deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…A further study by individual trabecular dynamics (ITD) analysis suggested that this could be caused by targeted bone formation that fills the perforations on trabecular plates. (49) Although such a change was not detected in the current study by analysis using SMI, in our future studies we plan to perform more advanced analysis, such as ITD analysis, to examine the dynamics of conversions between trabecular rodlike and plate-like structures in the estrogen-deficient bone in response to different treatment regimes.…”
Section: Discussionmentioning
confidence: 78%
“…A further study by individual trabecular dynamics (ITD) analysis suggested that this could be caused by targeted bone formation that fills the perforations on trabecular plates. (49) Although such a change was not detected in the current study by analysis using SMI, in our future studies we plan to perform more advanced analysis, such as ITD analysis, to examine the dynamics of conversions between trabecular rodlike and plate-like structures in the estrogen-deficient bone in response to different treatment regimes.…”
Section: Discussionmentioning
confidence: 78%
“…registered subvolumes through an individual trabecular dynamics (ITD) analysis, as described previously. (30) Briefly, the trabecular rods and plates were isolated using individual trabecular segmentation (ITS) analysis, (33) and the two registered subvolumes were compared to identify incidences of rod disconnection and plate perforation (measures of structural deterioration) and rod connection and plate perforation filling (measures of structural repair). (30) Additionally, the bone formation and resorption rates were also measured based on the registered subvolumes through in vivo dynamic bone histomorphometry analysis.…”
Section: Trabecular Dynamics Analysismentioning
confidence: 99%
“…Individual trabecular segmentation (ITS) analysis (29) was applied to isolate individual trabecular rod-like and plate-like elements, and changes in the volume, thickness, and connectivity of each trabecula over the first 4 weeks post-OVX were tracked through individual trabecular dynamics (ITD) analysis (27) (Figure 4A). Consistent with microstructural findings, virgin rats underwent a substantially higher rate of bone loss over the first 4 weeks post-OVX than reproductive rats (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…For each rat, sequential μCT images were registered to precisely align the trabecular features, as described in (20,25,26) , and a 1.5×1.5×1 mm trabecular subvolume located 1 mm distal to the growth plate was extracted from μCT images at 0 and 4 weeks post-OVX. The post-OVX changes of each individual trabecula, such as percent bone loss due to trabecular thinning, rod disconnection, or plate perforation, were quantified through an individual trabecular dynamics (ITD) analysis, as described in (27) . Trabeculae from all virgin or reproductive rats were pooled together, resulting in a total of 4,752 trabeculae in the virgin and 1,564 trabeculae in the reproductive group.…”
Section: Methodsmentioning
confidence: 99%